Synthesis, characterization, and in vitro cytotoxic activities of benzaldehyde thiosemicarbazone derivatives and their palladium(II) and platinum(II) complexes against various human tumor cell lines - Hernández Gorritti, Wilfredo Román (2008)
The palladium (II) bis-chelate Pd mathematical equation and platinum (II) tetranuclear mathematical equation complexes of benzaldehyde thiosemicarbazone derivatives have been synthesized, and characterized by elemental analysis and IR, FAB(+)-mass and NMR (¿1H, ¿13C) spectroscopy. The complex mathematical equation [HL2 = m-CN-benzaldehyde thiosemicarbazone] shows a square-planar geometry with two deprotonated ligands (L) coordinated to PdII through the nitrogen and sulphur atoms in a transarrangement, while the complex mathematical equation [HL4 = 4-phenyl-1-benzaldehyde thiosemicarbazone] has a tetranuclear geometry with four tridentate ligands coordinated to four PtII ions through the carbon (aromatic ring), nitrogen, and sulphur atoms where the ligands are deprotonated at the NH group. The in vitro antitumor activity of the ligands and their complexes was determined against different human tumor cell lines, which revealed that the palladium (II) and platinum (II) complexes are more cytotoxic than their ligands with IC50 values at the range of 0.07–3.67¿µM. The tetranuclear complex mathematical equation, with the phenyl group in the terminal amine of the ligand, showed higher antiproliferative activity (CI50 = 0.07–0.12¿µM) than the other tested palladium (II) complexes.